Change in the managerial efficiency and management technology of hotels: An application to Thailand - Akarapong Untong (2018)
This article estimates the change in managerial efficiency and management technology of a sample of hotels in Chiang Mai, Thailand, during 2002-2006. The study applies the data envelopment analysis (DEA) methodology proposed by Banker et al (1984) to examine managerial efficiency in 2002 and 2006. The Malmquist productivity approach developed by Färe et al (1992) is employed to evaluate the change in managerial efficiency and management technology over the same period. The results show that mediumsized and small hotels tend to be more managerially efficient than large hotels. The total factor productivity declined slightly owing to a lack of investment in management technology. Instead, the hotels in the sample concentrated on improving managerial effort. This shortfall in technology investment could hamper productivity in the longer term.